Northern tales : traditional stories of Eskimo and Indian peoples - Norman, Howard A. (New York : Pantheon Books, 1990)
A collection of folktales from the tribal peoples of Greenland, Canada, Russia, Alaska, and the polar region.
Includes bibliographical references (p. [335]-343).
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Eskimos -- Folklore; Indians of North America -- Folklore; Inuit -- Legends; Native Americans -- Folklore